ANALYSIS OF GENDER EQUALITY IN CHRISTIAN EDUCATION: A CASE STUDY OF IAKR PEMATANGSIANTAR STUDENTS - Purba, Melsa Yohana (Jurnal Review Pendidikan dan Pengajaran, 2025)
Gender equality remains a critical issue in higher education, particularly within faith-based institutions. This study examines perceptions and implementation of gender equality at Institut Agama Kristen Renatus (IAKR) Pematangsiantar, exploring theological, cultural, and institutional factors that influence its integration. Despite biblical principles supporting equality, traditional gender roles persist, affecting both students' and faculty members' views on the subject. This research employs a qualitative case study approach, involving 25 students, 10 lecturers, and 3 institutional leaders selected through purposive sampling. Data collection methods include in-depth interviews, classroom observations, and institutional document analysis. This triangulated approach ensures comprehensive insights into gender dynamics within the institution. Findings reveal a gap between theological acknowledgment of gender equality and its practical application. Cultural influences, particularly from Batak traditions, reinforce gender hierarchies, leading to hesitancy among female students to engage actively in academic discourse. Institutional barriers, such as underrepresentation of women in leadership and limited gender-sensitive policies, further hinder progress. However, some faculty members demonstrate efforts to integrate gender perspectives into pedagogy, signaling potential areas for reform. To address these challenges, the study recommends curriculum reform to incorporate gender-sensitive content, faculty training on inclusive pedagogical methods, and empowerment initiatives such as mentorship programs for female students. Institutional policies must also be strengthened to promote gender inclusivity at all levels. By aligning Christian theological principles with contemporary gender discourse, IAKR Pematangsiantar can foster a more equitable academic environment, serving as a model for gender-responsive Christian higher education.